Skala Produksi Jagung (Zea mays spp) Di Kecamatan Gunung Sugih Kabupaten Lampung Tengah - Rozi, Pahrol; Saty, Fadila Marga; Fitriani, Fitriani; Apriyani, Marlinda (CV. ITTC INDONESIA, 2022)
Corn is one type of food crop that has high economic value. The purpose of this study was to analyze the cost and income of corn farming, to analyze the factors that influence corn production, to analyze the economies of scale for corn farming in Gunung Sugih District. This research was conducted in Gunung Sugih District, Central Lampung Regency. The sampling method uses probability sampling with 32 respondents. The data analysis method used is income analysis, analysis of production factors with the Cobb-Douglas production function and the level of business scale (return to scale). Based on the results of the analysis it is known that the average income of corn farming is IDR 10,148,235.09/ha. Production factors that significantly influence corn production in Gunung Sugih District are land area (X1) and seeds (X2). Corn farming activities are at the level of business scale in field II (constant return to scale), which means that if the use of production factors is added, it will result in an increase in production in the same proportion as the input allocation.